2017
DOI: 10.1371/journal.pone.0176616
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and access to kidney transplantation in patients starting dialysis: A prospective cohort study

Abstract: BackgroundObesity has been linked to poor access to medical care. Although scientific evidence suggest that kidney transplantation improves survival and quality of life in obese patients with end-stage renal disease (ESRD), few data exist on the impact of obesity on access to kidney transplantation in this population.ObjectivesWe aimed to characterize the relationships between body mass index (BMI) at the start of dialysis, changes in BMI after the start of dialysis, and either access to kidney transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…38 An analysis from the French Renal Epidemiology and Information Network showed that a BMI ≥31 kg/m 2 at the start of dialysis was associated with a lower likelihood of receiving a KT, and the likelihood decreased as BMI increased. 39 Although obese transplant recipients had a higher likelihood of delayed graft function and a slightly higher risk of graft loss compared with their nonobese counterparts, there was no significant difference in overall mortality. 40 Furthermore, patient survival was significantly better among all BMI categories, including obese and extremely obese groups of KT recipients, compared with dialysis patients who remained on the waiting list.…”
Section: Ob E S It Y Manag Ement Among Patients On D Ialys Ismentioning
confidence: 92%
See 1 more Smart Citation
“…38 An analysis from the French Renal Epidemiology and Information Network showed that a BMI ≥31 kg/m 2 at the start of dialysis was associated with a lower likelihood of receiving a KT, and the likelihood decreased as BMI increased. 39 Although obese transplant recipients had a higher likelihood of delayed graft function and a slightly higher risk of graft loss compared with their nonobese counterparts, there was no significant difference in overall mortality. 40 Furthermore, patient survival was significantly better among all BMI categories, including obese and extremely obese groups of KT recipients, compared with dialysis patients who remained on the waiting list.…”
Section: Ob E S It Y Manag Ement Among Patients On D Ialys Ismentioning
confidence: 92%
“…Many centers have adopted strict policies with regard to patients above threshold BMI of 30‐35 kg/m 2 , thus limiting the access to transplantation for obese dialysis patients . An analysis from the French Renal Epidemiology and Information Network showed that a BMI ≥31 kg/m 2 at the start of dialysis was associated with a lower likelihood of receiving a KT, and the likelihood decreased as BMI increased …”
Section: Obesity Management Among Patients On Dialysismentioning
confidence: 99%
“…Data from the French Renal and Epidemiology Information Network (REIN) indicate that, after adjustment for potential confounding variables, the likelihood of transplantation falls as BMI increases above 30 kg/m 2 . Patients with a BMI of > 31kg/m 2 are more likely to remain on dialysis than receive a kidney transplant (HR <1) . Beyond this, patients with a BMI ≥40 kg/m 2 were half as likely to undergo transplantation than those with a BMI between 21‐31 kg/m 2 .…”
Section: Weight Bias In Transplantation and Transplant Listingmentioning
confidence: 99%
“…Patients with a BMI of > 31kg/m 2 are more likely to remain on dialysis than receive a kidney transplant (HR <1) . Beyond this, patients with a BMI ≥40 kg/m 2 were half as likely to undergo transplantation than those with a BMI between 21‐31 kg/m 2 . Furthermore, in those with a BMI ≥30kg/m 2 each 1 kg/m 2 decrease in BMI is associated with a 9%‐11% increase in the likelihood of transplantation.…”
Section: Weight Bias In Transplantation and Transplant Listingmentioning
confidence: 99%
“…Nearly 60% of all kidney transplant recipients are overweight or obese with male predominance [4]. It was proven that obesity limits, or at least delays, access to kidney transplantation [5]. Bariatric surgery is considered a safe method to achieve rapid and sustainable weight loss before kidney transplantation [6].…”
Section: Introductionmentioning
confidence: 99%